Kesan dasar kewangan terhadap jenis kontrak pembiayaan perbankan Islam - Muhammad Fidlizan, Mohd Hussin Mohd Yahya, Abdul Razak Azila, (N/A, 2013)
Kesan dasar kewangan terhadap jenis kontrak pembiayaan perbankan Islam by Muhammad Fidlizan, Mohd Hussin Mohd Yahya, Abdul Razak Azila,